KAJIAN FRAMING PEMBERITAAN DEFORESTASI DAN EKSPANSI LAHAN SAWIT: ANALISIS KOMPARASI MEDIA INDONESIA - Alvin Subagyo, Christian (Metahumaniora, 2026)
The This study aims to analyze the ecological framing of deforestation and palm oil expansion in Indonesian online media from an ecolinguistic perspective. The research data consist of seven news articles published by CNN Indonesia, Kompas, Detik, Tempo, Liputan6, TribunNews, and BBC Indonesia. The study employs a qualitative descriptive method using Stibbe’s stories we live by framework as the primary analytical approach. The analysis focuses on ideology, framing, evaluation, identity, conviction, erasure, and salience in order to reveal how environmental issues are represented in media discourse. The findings indicate that each media outlet constructs different ecological framings of deforestation. The study identifies diverse stories we live by that reflect the ideological orientations of each media outlet. Furthermore, the study proposes alternative narratives that position forests as shared living spaces and advocate development within ecological limits. These findings demonstrate that the media not only disseminate environmental information but also shape public understanding of the relationship between humans and nature.